Revealing the hidden biodiversity of Antarctic and the Magellanic Sub-Antarctic Ecoregion: A comprehensive study of aquatic invertebrates from the BASE Project - Rosenfeld, Sebastian; Maturana, Claudia S.; Ganan, Melisa; Carcamo, Javier Rendoll; Diaz, Angie; Contador Mejias, Tamara Andrea; Aldea Venegas, Cristian Leonardo; Gonzalez-Wevar, Claudio; Orlando, Julieta; Poulin, Elie (My University, 2023)
BackgroundAntarctica, its outlying archipelagoes and the Magellanic Subantarctic (MSA) ecoregion are amongst the last true wilderness areas remaining on the planet. Therefore, the publication, citation and peer review of their biodiversity data are essential. The new Millennium Institute Biodiversity of Antarctic and Subantarctic Ecosystems (BASE), a Chilean scientific initiative funded by the National Agency of Research and Innovation, contributes 770 new records of aquatic invertebrates as a point of reference for present-day biodiversity research at these latitudes.New informationThe occurrence dataset presented here has never been released before and is the result of the systematic recording of occurrences of several taxa across the Antarctic, Subantarctic and Magellanic Subantarctic ecoregions. We collected data from marine and freshwater invertebrates across numerous samplings from 2008 to 2023. From the 770 occurrences, we identified 160 taxa, 125 at species level and 35 at the genus level. The database has been registered in the Global Biodiversity Information Facility (GBIF). The publication of this data paper was funded by the Belgian Science Policy Office (BELSPO, contract n(degrees)FR/36/AN1/AntaBIS) in the Framework of EU-Lifewatch as a contribution to the SCAR Antarctic biodiversity portal (biodiversity.aq)
Keywords: cape horn biosphere reserve; freshwater ecosystems; gbif; macroinvertebrates; southern ocean